2016
DOI: 10.1007/s00403-016-1696-x
|View full text |Cite
|
Sign up to set email alerts
|

The IKKα-dependent non-canonical pathway of NF-κB activation is constitutively active and modulates progression-related functions in a subset of human melanomas

Abstract: Owing to activation of several resistance-mediating pathways including NF-κB signaling, metastasized melanoma is almost universally resistant against chemotherapy. Given that blocking of NF-κB either by proteasome-, pan-IKK- or selective IKKβ-inhibitors may increase the susceptibility of melanoma cells to chemotherapy, we have assessed the role of the second kinase within the IKK complex, IKKα. While expression of IKKα and overall activation of NF-κB were heterogeneous, the IKKα-specific p100/p52 processing wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…One study assessed the role of IKKα in melanoma patients [105]. The expression of IKKα and overall activation of NF-κB were heterogeneous.…”
Section: Ikk Inhibition By Peptides/bio-molecules-another Approach For Suppressingmentioning
confidence: 99%
See 1 more Smart Citation
“…One study assessed the role of IKKα in melanoma patients [105]. The expression of IKKα and overall activation of NF-κB were heterogeneous.…”
Section: Ikk Inhibition By Peptides/bio-molecules-another Approach For Suppressingmentioning
confidence: 99%
“…• IKKα siRNA: Reduced doxorubicin-induced NF-κB activation, constitutive and TNFα-stimulated expression of CXCL8 and ICAM-1, and cell migration in melanoma cells [105].…”
Section: Abbreviationsmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are an important molecular mediator of cell genetic changes, and are directly or indirectly associated with the occurrence and development of a number (6)(7)(8)(9)(10). Previous studies have indicated that Tudor-SN has a close association with lipid metabolism, and that the expression of lipoprotein in liver cells can be affected through adjustment of lipid metabolism-associated genes (11,12).…”
Section: Introductionmentioning
confidence: 99%